Immune-mediated mechanisms of the inflammatory response in women with combined infections of the lower genital tract - G. B. Dikke; A. A. Sukhanov; I. I. Kukarskaya; V. V. Ostromenskii (Акушерство, гинекология и репродукция, 2021)
Aim: to increase the effectiveness of combination therapy and reduce frequency of recurrences of inflammatory diseases in the lower genital tract of combined etiology.Materials and Мethods. There was conducted a prospective, randomized, blind, comparative clinical study. 80 women with vaginal microbiota disorders were examined randomized into 2 groups: group I (n = 40) – antibiotic therapy was carried out in combination with the preparation Superlimph, group II (n = 40) – a standalone antibacterial therapy; group III consisted of 20 patients lacking gynecological diseases considered to provide with control laboratory parameters. Clinical and laboratory methods were used: microscopy of vaginal smears, detection of viruses and sexually transmitted infections, measurement of serum cytokine levels – interleukins (IL-1â, IL-2, IL-4, IL-6, IL-8, IL-10), tumor necrosis factor alpha, (TNF-á), interferon gamma (IFN-ã).Results. It was found that clinical recovery occurred in 90.0 and 70.0 % of patients in group I and group II (р = 0.02), respectively. Microbiological recovery was observed in 100.0 and 67.5 % of patients, respectively (р = 0.003). In group I, the isolation of herpes simplex virus type 2 was found in 80.0 and 45.2 % of patients before and after treatment (p < 0.001), respectively, whereas in group II – in 82.5 and 77.5 %, respectively (p = 0.58), between groups – p < 0.001. Before treatment the level of all cytokines, excepting IFN-ã, was higher than the reference values in both groups: in group I, their magnitude decreased after treatment (p < 0.001) and corresponded to the reference values; in group II no changes occurred. Three months after treatment, no relapses were observed in group I, whereas frequency of relapses in group II was 22.5 %, within 1 year – 0 and 35.1 %, respectively. Predictors of recurrent dysbiosis (IL-2, IL-6 and TNF-á in increased concentrations after a course of treatment) were identified.Conclusion. Treatment with a combined broad-spectrum antimicrobial drug along with topical immunomodulatory agent containing exogenous cytokines is an effective strategy for treating concomitant dysbiosis and preventing relapse.